'It's not just about death': changing attitudes and knowledge of palliative care in neonatal units. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Kelly, Paula; Twamley, Katherine; Moss, Rebecca; Mancini, Alexandra; Bluebond-Langner, Myra; Koh, Michelle
Abstract : Background: In an effort to facilitate improved and earlier access to palliative care (PC) for babies and their families, a 4 h educational workshop on the principles, practice and resources in PC was offered in 21 neonatal units across London. Each workshop was tailored to ensure locally relevant information. This paper assesses the impact of these workshops. Aim: To evaluate the impact of a short 4 h workshop on the attitudes towards PC and knowledge of services among neonatal clinical staff. Methods: Before and after each workshop, attendees completed a survey of open and closed questions to assess changes in attitudes and knowledge. Descriptive statistical analyses were conducted with SPSS, and thematic analysis of open-ended responses with NVIVO software. Results: 331 healthcare professionals attended the sessions, and 264 (80%) completed questionnaires. The majority of attendees were experienced neonatal nurses working in NICU, with limited experience making referrals to PC services. Statistical tests showed significant (p<0.05) shifts in attitudes and knowledge. After the session, 80% of respondents felt confident referring to palliative care services, compared with 46% before. An additional 20% of respondents selected 'diagnosis' as the appropriate time to refer to PC. Analysis of open text responses revealed a shift in attitude after the sessions from a focus on dying/end of life, towards integrating PC as part of a holistic treatment plan. Over 79% of respondents reported that the workshop met their learning needs with regard to PC services and referral procedures. Conclusions: A short locally delivered workshop can change attitudes and increase knowledge in neonatal staff. Further work is being conducted to assess the impact of such changes on clinical practice, including referral to community and specialist PC services.